Soil amendment with compost and crop growth stages influenced heavy metal uptake and distribution in maize crop grown on lead-acid battery waste contaminated soil. (2018)
Heavy metal contamination of agricultural soils poses serious risk to human health through food chain. Immobilization technique to reduce metal bioaccumulation in plant tissues is being promoted. Field experiment was carried out on heavy metal contaminated site to test for the efficacy of different organic amendments (Mexican sunflower compost (MSC) and Cassava peel compost (CPC) applied at 0, 20 and 40 t/ha) and inorganic fertilizer (NPK; 20:10:10 at 100 kg Nitrogen /ha) in metal immobilization and uptake by maize crop at different growing stages (one, two month(s) after planting (1MAP, 2MAP) and at harvesting). Compost amendments generally reduced heavy metal accumulation in maize crop unlike NPK and control where high metal toxicity led to plant death at 2MAP. Pb was highly accumulated at every growing stage followed by Cd while Cr concentration was below the detection limit at harvesting. Bioaccumulation and transfer factors were found to depend on maize growing stage with higher accumulation at 1MAP. Percentage Pb accumulation in the shoot was more at 1MAP but reversed at 2MAP and harvesting with higher accumulation in the root. Application of MSC and CPC at 20 and 40 t/ha reduced Pb accumulation in maize by 37.8–64.7% compared with control and the reduction at harvesting was more significant than those recorded at 1MAP and 2MAP, The study concluded that compost reduced heavy metals accumulation in maize crop and that metal accumulation depends on maize growth stage.